PENGARUH EXPERIENTIAL MARKETING DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN - Isran Riski Alfasiri; Meyzi Heriyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The research conducted at RM. Pondok Gurih Pekanbaru where located in Jl. Sudirman No. 22. The problem in this study is number of buyers has decreasing, percentage of target achievement has decreased, complaints from consumer and the failure of the company’s sales target has not been achieved, this study aims to determine the effect of experiential marketing and product quality on consumer satisfaction at RM. Pondok Gurih Pekanbaru.. In this study use quantitive descriptive with SPSS program. The population in this is are consumers at RM. Pondok Gurih Pekanbaru. The sampling technique chosen is slovin Formula with a sample 100 respondents. Hypothesis testing uses a simple linear analysis method and multiple analysis with result showing that experiential marketing and product quality have a positive and significant effect on consumer satisfaction at RM. Pondok Gurih Kota Pekanbaru. With the calculation of the coefficient of determination (R2)experiential marketing on consumer satisfaction the value of R square is 0,543 or 54,3% and product quality on consumer satisfaction the value of R square is 0,500 or 50% and coefficient of determination (R2) experiential marketing and quality product on consumer satisfaction the value of R square is 0,723 or 72,3%. This show that the experiential marketing and quality product gives an effect of 72,3% on consumer satisfaction at RM. Pondok Gurih Kota Pekanbaru, while remaining 27,7% is effected by other variables that are not examined in this study. Keywords: Experiential Marketing, Quality Product, Consumer Satisfaction